2004
DOI: 10.1111/j.1440-1746.2004.03591.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing epidemiology of gastroesophageal reflux disease in the Asian–Pacific region: An overview

Abstract: Gastroesophageal reflux disease (GERD) is a common disease in the West, which now appears to be also increasing in prevalence in the Asian Pacific region. The reasons for this changing epidemiology are two-fold: an increased awareness among doctors and patients, and/or a true increase in the prevalence of the disease. Prevalence rates of reflux esophagitis (RE) of up to 16% and prevalence of GERD symptoms of up to 9% have been reported in the Asian population. However, the frequency of strictures and Barrett's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 30 publications
(37 reference statements)
1
64
1
3
Order By: Relevance
“…Batı toplumlarında üst gastrointestinal sistem (GİS) endoskopisi yapılan hastaların %15-25'inde özofajit bulunduğu rapor edilmiştir (11). Asya' da yapılan çalışmalarda ise bu sıklığın %0.8-16.3 gibi çok daha az sıklıkta görüldüğü bildirilmekte ve batılaşmayla beraber sıklığın giderek arttığı iddia edilmektedir (11,12).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Batı toplumlarında üst gastrointestinal sistem (GİS) endoskopisi yapılan hastaların %15-25'inde özofajit bulunduğu rapor edilmiştir (11). Asya' da yapılan çalışmalarda ise bu sıklığın %0.8-16.3 gibi çok daha az sıklıkta görüldüğü bildirilmekte ve batılaşmayla beraber sıklığın giderek arttığı iddia edilmektedir (11,12).…”
Section: Discussionunclassified
“…Asya' da yapılan çalışmalarda ise bu sıklığın %0.8-16.3 gibi çok daha az sıklıkta görüldüğü bildirilmekte ve batılaşmayla beraber sıklığın giderek arttığı iddia edilmektedir (11,12). Normal sağlıklı popülasyonun rutinde gastroskopiye gitmemesinden dolayı özofajitin gerçek prevalansını saptamak biraz daha zordur.…”
Section: Discussionunclassified
“…In the Eastern world, 3-7% of the adult population complains of the symptoms once or more per week (3,4). However, its prevalence has gradually increased (5), and domestic research reports have also indicated increasing trends (6).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the prevalence of GERD in Asia is increasing [4,5] . In China, the majority of patients with reflux symptoms are investigated by endoscopy and, if no clear endoscopic findings are identified, they are often diagnosed as having chronic gastritis (CG) rather than NERD because this diagnosis is thought to be more acceptable to the patient.…”
Section: Introductionmentioning
confidence: 99%